Problem formulation for gene drive mosquitoes designed to reduce malaria transmission in Africa: results from four regional consultations 2016–2018 - Teem, John L. (Malar J, 2019)
BACKGROUND: Gene drive mosquitoes have been proposed as a possible means to reduce the transmission of malaria in Africa. Because this technology has no prior use-history at this time, environmental risk assessments for gene drive mosquitoes will benefit from problem formulation—an organized and ordered process to identify protection goals and potential pathways to harm to the environment, or animal or human health. Recognizing this need, the New Partnership for Africa’s Development (NEPAD), with support from African and international partners, organized four regional consultative workshops in Africa to initiate this process. METHODS: The workshops were attended by a diverse set of participants and stakeholders, including scientists, ethicists, health professionals, government regulators in the fields of environment health and biosafety as well government policymakers, who met for 4 days to deliberate on protection goals and pathways relevant to the use of gene drive mosquitoes for malaria control. The goal of the workshops was not to produce a comprehensive and detailed environmental risk assessment of gene drive mosquitoes, but rather to introduce problem formulation as a tool to the stakeholder community, and to serve as a starting point for conducting systematic environmental risk assessments in the future, identifying protection goals related to gene drive mosquitoes that are particular to African stakeholders. RESULTS: Participants in the workshops frequently identified human health and biodiversity as being relevant broad protection goals. Results of the deliberations provide insight into the concerns of African participants at an early stage in the development of gene drive organism/products that should be instructive to developers using this technology. CONCLUSIONS: In general, the African participants of the consultations had a precautionary perspective with regard to environmental risk assessment of gene drive technology. As gene drive technology develops, protection goals will become further refined and candidate products will be further defined. These workshops represent only the beginning of a continuing process that will ultimately inform environmental risk assessment for gene drive mosquitoes to control malaria in Africa.